IIIT's Integration of Knowledge Summer Program 2023 - Hasan, Md. Mahmudul; Zawawi, Boshra (Islamic Society of North America, 2023)
IIIT summer programs are generally designed for (active) graduate students who wish to become better acquainted with various debates involving Islam, Muslims, and the modern world. Participants interacted with the instructors and peers both as individual and group learners.